Methane management in sewage treatment - Cookney, Joanna (Cranfield University, 2011)
Poly-di-methyl-siloxane (PDMS) hollow fibre membrane modules were designed and built for the specific de-gassing of real and synthetic process liquids to understand: (i) the feasibility of operation; and (ii) classify the mass transfer characteristics to aid design at full scale. Liquid saturated with pure methane or a binary methane and carbon dioxide mixture was introduced into the shell side of the extraction unit, whilst sweep gas or vacuum was employed counter-currently as a stripping medium. From data analysis of operation in both anaerobic effluents obtained from Expanded Granular Sludge Blanket (EGSB) reactor and synthetic liquids, when operating under optimum conditions 93% of methane and 88% of carbon dioxide was recovered. The obtained data indicate that the extraction process is controlled by diffusivity of gases through the PDMS membrane and is proportional to the thickness of membrane wall. When applying vacuum to promote methane mass transfer, the process was highly sensitive to vacuum pressure; the highest de-gassing efficiency was recorded under the lowest absolute vacuum pressure. However, when vacuum was replaced by sweep gas, the process was insensitive to changes in gas velocity. When utilising PDMS membrane contactor for de-gassing of EGSB effluent, the net electrical output achieved by the EGSB increased by c. 24% and indicates that by integrating methane recovery, treatment of domestic wastewater using low temperature EGSB processes can become carbon positive. The potential of directing recovered methane to porous hollow fibre membrane absorbers and upgrading to national gas (NG) standards to use in national gas grid or as a vehicle fuel has been demonstrated.
Keywords: Methane recovery; poly-di-methyl-siloxane; biogas; anaerobic effluent; hollow fibre membrane contactors; methane management; carbon dioxide